A Handbook to Support the Sexual and Reproductive Health Needs of Factory Women Migrant Workers - Miles, Lilian; Endut, Noraida; Tim, Freeman; Kelvin, Ying; Lai, Wan Teng; Mat Yasin, Suziana Mat Yasin (Universiti sains malaysia, 2022)
This Handbook is the product of a five-year research programme, funded at different phases by three funding agencies, investigating ways in which the sexual and reproductive health (SRH) needs of Malaysia's factory women migrant workers can be supported. Sexual and reproductive health is regarded as a human right, essential to human development and the achievement of the UN Sustainable Development Goals. It is enshrined in the 1994 International Conference on Population and Development (ICPD) Program of Action, the 1995 Beijing Declaration and Platform for Action and the UN Sustainable Development Goals. The United Nations Population Fund (UNFPA) defines good sexual and reproductive health as "a state of complete physical, mental and social well-being in all matters relating to the reproductive system. It implies that people are able to have a satisfying and safe sex life, the capability to reproduce and the freedom to decide if, when, and how often to do so. To maintain one's sexual and reproductive health, people need access to accurate information and the safe, effective, affordable and acceptable contraception method of their choice. They must be informed and empowered to protect themselves from sexually transmitted infections. And when they decide to have children, women must have access to skilled health care providers and services that can help them have a fit pregnancy, safe birth and healthy baby. Every individual has the right to make their own choices about their sexual and reproductive health." Our research shows that women migrant workers in Malaysia are a marginalised population and vulnerable to poor SRH. Poor SRH impacts on these women's well-being and their ability to work. Yet, many women migrant workers cannot afford healthcare to address poor SRH, are unfamiliar with the local health system and do not have access to SRH information, education or counselling. They are reluctant to mention that something is wrong or discuss SRH conditions with managers and supervisors. As a result, many women migrant workers suffer from untreated reproductive health conditions, such as breast and cervical diseases, urinary tract infections, menstruation problems or unwanted pregnancies. Many of these conditions can be prevented. Forced testing against pregnancy, prohibitions against getting pregnant and imprisonment and deportation in the event of pregnancy and abortion all violate the SRH rights of women migrant workers. So too, does differential treatment on the part of health care providers against women migrant workers seeking medical treatment for SRH or when employment contracts prohibit marriage and pregnancies for migrant workers.